Empowering Future Entrepreneurs: Self-Confidence and Creativity as Key Factors in Entrepreneurial Mindset Formation for Vocational Students - Dini Sumanti; Yeka Hendriyani; Muhammad Giatman; Henny Yustisia (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study examines the influence of self-confidence and creativity on the entrepreneurial mindset of vocational students. As vocational education increasingly aims to equip students for dynamic economic environments, fostering entrepreneurial thinking is essential. The research was conducted at SMKN 1 Guguk using a quantitative survey design involving 91 automotive program students. Data were analyzed through multiple regression and Partial Least Squares Structural Equation Modeling (PLS-SEM). The regression analysis revealed that self-confidence and creativity collectively explain 80.9% of the variance in entrepreneurial mindset (R² = 0.809). The model was statistically significant (F = 186.304, p 0.05), with both self-confidence (B = 0.687, t = 8.947, p = 0.000) and creativity (B = 0.328, t = 4.326, p = 0.000) showing significant positive effects. PLS-SEM results further confirmed the model's reliability, with all indicators demonstrating strong outer loadings ( 0.85) and construct validity. The findings suggest that self-confidence plays a more dominant role than creativity in shaping students' entrepreneurial mindset. These results highlight the need for vocational schools to incorporate learning models—such as Project-Based Learning and Teaching Factory—that strengthen students’ psychological readiness alongside technical skills. In conclusion, enhancing self-confidence and creativity through structured educational approaches can significantly support the development of entrepreneurial competencies among vocational students, preparing them to pursue innovation and opportunity in real-world contexts.